Sex differences in dietary intake in British Army recruits undergoing phase one training. Issue 1 (10th December 2019) - Chapman, Shaun; Roberts, Justin; Smith, Lee; Rawcliffe, Alex; Izard, Rachel
Abstract: Background: British Army Phase One training exposes men and women to challenging distances of 13.5 km·d − 1 vs. 11.8 km·d − 1 and energy expenditures of 4000 kcal·d − 1 and 3000 kcal·d − 1, respectively. As such, it is essential that adequate nutrition is provided to support training demands. However, to date, there is a paucity of data on habitual dietary intake of British Army recruits. The aims of this study were to: (i) compare habitual dietary intake in British Army recruits undergoing Phase One training to Military Dietary Reference Values (MDRVs), and (ii) establish if there was a relative sex difference in dietary intake between men and women. Method: Researcher led weighed food records and food diaries were used to assess dietary intake in twenty-eight women (age 21.4 ± 3.0 yrs., height: 163.7 ± 5.0 cm, body mass 65.0 ± 6.7 kg), and seventeen men (age 20.4 ± 2.3 yrs., height: 178.0 ± 7.9 cm, body mass 74.6 ± 8.1 kg) at the Army Training Centre, Pirbright for 8-days in week ten of training. Macro and micronutrient content were estimated using dietary analysis software (Nutritics, Dublin) and assessed via an independent sample t-test to establish if there was a sex difference in daily energy, macro or micronutrient intakes. Results: Estimated daily energy intake was less than the MDRV for both men and women, with men consuming a greater amount of energy compared with women (2846 ± 573 vs. 2207 ± 585 kcal·day − 1, p < 0.001). Both sexes under consumed carbohydrate (CHO) when data was expressed relative to body mass with men consuming a greater amount than women (4.8 ± 1.3 vs. 3.8 ± 1.4 g·kg − 1 ·day − 1, p = 0.025, ES = 0.74). Both sexes also failed to meet MDRVs for protein intake with men consuming more than women (1.5 ± 0.3 vs. 1.3 ± 0.3 g·kg − 1 ·day − 1, p > 0.030, ES = 0.67). There were no differences in dietary fat intake between men and women (1.5 ± 0.2 vs. 1.5 ± 0.5 g·kg − 1 ·day − 1, p = 0.483, ES = 0.00). Conclusions: Daily EI in men and women in Phase One training does not meet MDRVs. Interventions to increase macronutrient intakes should be considered along with research investigating the potential benefits for increasing different macronutrient intakes on training adaptations.